Microneedling plus topical insulin for atrophic acne scar revision in Fitzpatrick skin phototype IV: case report - Kiki Septiafni; Sarah Diba Zulkarnain; Yuli Kurniawati; Soenarto Kartowigno; Nopriyati Nopriyati (Sociedade Brasileira de Dermatologia (SBD), 2023)
Atrophic acne scars result from an abnormal wound-healing response that can be treated with microneedling (MN). Insulin may play a role in wound healing. The effectiveness and safety of combining MN with topical insulin as an alternative therapy for atrophic acne scar revision have not yet been widely reported. We report the case of a 33-year-old woman with an atrophic acne scar on the middle third of her face. The patient was treated with MN and topical insulin for four sessions at two-week intervals. MN plus insulin can be considered an alternative for acne scar revision.